Demand Trends for The Development of Mobile Applications for Public Electric Vehicle Charging Stations from The Perspective of Users in The Central Region of Thailand - Naovakoon, Natpimon; chaiyasoonthorn, wonchanok; Chaveesuk, Singha (Journal of KMITL Business school, 2025)
The research, titled Demand Trends for the Development of Mobile Applications for Public Electric Vehicle Charging Stations from the Perspective of Users in the Central Region of Thailand, aims to: 1) compare the demand trends for application development based on user demographics, and 2) identify factors influencing these trends. The research sampled 400 EV users in the central region of Thailand, all with at least three months of experience using EV charging station applications. Data were collected through a questionnaire with a reliability coefficient (Cronbach’s alpha) of 0.92. Descriptive statistics (frequency, percentage, mean, standard deviation) and inferential statistics (t-test, One-way ANOVA, and multiple linear regression analysis) were employed for data analysis. The findings reveal significant impacts of demographic factors, such as age, gender, and education level, on user demand for application development, particularly in service quality and system efficiency. Male users emphasize speed and functionality, while female users prioritize ease of use and accurate information. Younger users (18–37 years) favor modern features like real-time station status updates, whereas older users (38 years and above) focus on simplicity and essential functions. The study also highlights that perceived usefulness, ease of use, and performance expectations strongly influence user demand. These insights provide practical guidelines for application developers and stakeholders to improve EV charging application systems, ensuring they meet diverse user needs in the central region of Thailand.